Rapid and selective UV spectrophotometric method for the analysis of ceftazidime - Moreno, Andréiade Haro [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (Oxford University Press (OUP), 2009)
A new UV spectrophotometric method was developed for quantitative evaluation of ceftazidime preparations. The UV detector was set at 255 nm. Beer's law is obeyed in the concentration range of 7.0-14.0 μg/mL. The method was found to be selective, linear, accurate, and precise in the specified ranges. Intra- and interday variability for the method were <2% relative standard deviation. Common excipients used as additives in pharmaceutical preparations do not interfere with the proposed method. This method was successfully used for quantification of ceftazidime in pure form and in pharmaceutical preparations.